THE RELATIONSHIP OF SOCIAL, ECONOMIC, AND ENVIROMENTAL FACTORS WITH STUNTING OCCURRENCE IN TODDLERS - Indramaya Tongkonoo; Margaretha Solang; Dewi Wahyuni K Baderan (Jambura Journal of Health Sciences and Research, 2021)
The incidence of stunting under five is a major nutritional problem faced by Indonesia. The research aimed to determine relationship of the social, economic, and environmental factors related with   stunting occurrenceintoddlers 10-59 months at Health Centers Gorontalo District. This research was done on the population of toddlers who experience stunting in 2019 recorded in 7Health Centers. The data was collected from 98 samples by applying the purposive sampling method. The research instrument was done by using a questionnaire. Data analysis employs univariate, bivariate analysis and chi-square test with the help of software SPSS version 21. The result showed that the social factors, namely mother's education with the p-value of 0,000 OR =  12,375 CI = 4,560-33,584, and economic factors, namely income with the p-value of 0,000 OR = 11,719 CI = 3,652 â€“ 38,605 and environmental factors, namely  waste disposal facilities with the p-value of 0,000 OR = 12,813 CI = 4,815 -34,097. Based on these result, it can be stated that social factors, especially mother's education, economic factors, especially income, and  environmental factors, especially waste disposal facilities have a significant relationship with stunting occurrence in toddlers 10-59 months at the Health Centers Gorontalo District.